2021
DOI: 10.1016/j.xinn.2021.100139
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and low temperature associated with case fatality of COVID-19: A nationwide retrospective cohort study in China

Abstract: A national retrospective cohort study was performed to quantify the effects of environmental exposure -Low temperature was observed to be associated with COVID-19 case fatality -Exposure to ambient air pollution played a nonnegligible part in COVID-19 case fatality -COVID-19 patients were more susceptible to external environmental stimulus as COVID-19 progressed from the period of symptom onset to diagnosis ll www.cell.com/the-innovation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Our results suggest that increase in the temperature decreases the viability, stability, survival of SARS-CoV-2 pathogens and transmission of COVID-19. Such inverse associations of COVID-19 viral infections with air temperature have been reported also by ( Tian et al, 2021 ; Srivastava, 2021 ; Jiang et al, 2021 ; Li et al, 2020 ; Benedetti et al, 2020 ; Bolaño-Ortiz et al, 2020 ; Sanchez-Lorenzo et al, 2021 ; Luo et al, 2020 ). Although most studies indicated an inverse association of viral community spread with temperature, some findings reported a positive relationship between temperature and the number of COVID19 cases ( Menebo, 2020 ; Li et al, 2020 ; Xie and Zhu, 2020 ; Bashir et al, 2020 ; Xie and Zhu, 2020 ; Pani et al, 2020 ; Islam et al, 2021 ) and few studied found no correlation ( Briz-Redón and Serrano-Aroca, 2020 ).…”
Section: Resultssupporting
confidence: 64%
“…Our results suggest that increase in the temperature decreases the viability, stability, survival of SARS-CoV-2 pathogens and transmission of COVID-19. Such inverse associations of COVID-19 viral infections with air temperature have been reported also by ( Tian et al, 2021 ; Srivastava, 2021 ; Jiang et al, 2021 ; Li et al, 2020 ; Benedetti et al, 2020 ; Bolaño-Ortiz et al, 2020 ; Sanchez-Lorenzo et al, 2021 ; Luo et al, 2020 ). Although most studies indicated an inverse association of viral community spread with temperature, some findings reported a positive relationship between temperature and the number of COVID19 cases ( Menebo, 2020 ; Li et al, 2020 ; Xie and Zhu, 2020 ; Bashir et al, 2020 ; Xie and Zhu, 2020 ; Pani et al, 2020 ; Islam et al, 2021 ) and few studied found no correlation ( Briz-Redón and Serrano-Aroca, 2020 ).…”
Section: Resultssupporting
confidence: 64%
“…Similarly, an early ecologic study conducted in Italy found that an increase of 1 μg/m 3 in the long-term mean PM 2.5 concentration (µg/m 3 ) was associated with a 9% (95% CI: 6–12%) increase in COVID-19 related mortality ( Coker et al 2020 ). Additional analyses have similarly reported increases in COVID-19 mortality associated with PM 2.5, including studies conducted in the United States (Berg, Romer Present, and Richardson 2021; Garcia et al 2021 ; Liang et al 2020 ; Kim and Bell 2021 ) and internationally ( Konstantinoudis et al 2021 ; Cole, Ozgen, and Strobl 2020 ; Yao et al 2020 ; Dales et al 2021 ; Valdes Salgado et al 2021 ; Tian et al 2021 ; Rodriguez-Villamizar et al 2021 ; Elliott et al 2021 ; Bray, Gibson, and White 2020 ; Tchicaya et al 2021 ; Dettori et al 2021 ; Lopez-Feldman, et al 2021 ), as well as a recent meta-analysis ( Zang et al 2022 ). Only a few studies have reported no association ( Millett et al 2020 ; Adhikari and Yin 2020 ; Rodriguez-Villamizar et al 2021 ; Elliott et al 2021 ; Kim and Bell 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…For example, temperature and humidity are related to the spread of severe acute respiratory syndrome (SARS)(Rahimi et al 2021 ; Rosario et al 2020 ; Sarkodie and Owusu 2020 ); some scholars believe that the spread of influenza will increase around cooler, drier air (Haque and Rahman 2020 ; Shen et al 2021 ), and other scholars believe that the high wind speeds that cause atmospheric instability seem to reduce the number of infected people and promote the spread of air pollution (Mario Coccia 2021 ; Coccia 2021b ). In addition, air pollution has been also widely considered to be an important factor in increasing the risk of adverse health outcomes (Du et al 2021 ; Tian et al 2021 ), such as ischemic heart disease, chronic obstructive pulmonary disease, and respiratory infection (Manisalidis et al 2020 ; Tian et al 2021 ; Wu et al 2016 ). Emerging evidence suggests potential links between exposure to polluted air and the epidemic of COVID-19(Chen et al 2021 ; Chen et al 2020 ; Konstantinoudis et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%